Pengaruh Likuiditas, Modal Kerja, Pertumbuhan Penjualan Dan Ukuran Perusahaan Terhadap Profitabilitas Pada Perusahaan Manafaktur Sektor industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2019-2021. - Wilsa Betterment Road Sitepu; Cipra Simanjuntak; Erika Novelina Lumban Gaol (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was conducted with the aim of obtaining information related to the effect of Liquidity, Working Capital, Sales Growth and Company Size on Profitability in manufacturing companies engaged in the consumer goods industry sector which are listed on the Indonesia Stock Exchange for the 2019-2021 period. Purposive sampling technique was chosen to collect data in the study. After conducting research, the results obtained are: 1. Liquidity does not have a significant and positive effect on Profitability, 2. Working capital does not have a significant and negative effect on Profitability, 3. Sales Growth does not have a significant and positive effect on Profitability, 4 5. Company size does not significantly and negatively affect Profitability, 5. Liquidity, Working Capital, Sales Growth and Company Size influence significantly and positively simultaneously on Profitability. The test results of the Classical Assumption Test which go through the process of Normality Test, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, Coefficient (R2), Hypothesis (F Test), Hypothesis (T Test). Adjusted R Square has a 35% effect on Profitability and the remaining 65% is influenced by other variables, namely TATO, DR and DER. Keywords: Profitability; Liquidity; Working capital; Sales Growth; Company Size.